Assessing Measurement Error in Key Informant Reports: A Methodological Note on Organizational Analysis in Marketing - Phillips, Lynn W. (Journal of Marketing Research, 1981)
The author examines the reliability and validity of measures of organizational characteristics used in previous marketing studies in the areas of strategic planning and distribution channels. Key informants in 506 wholesale-distribution companies provided reports on (1) characteristics of the firm's product portfolio and (2) characteristics of the firm's power-dependence relations with its major suppliers and customers. In contrast to previous investigations, which sampled only a single informant per unit of analysis, data were collected from multiple informants in each firm. Results showed that informant reports often achieved convergent and discriminant validity when variance due to methods factors was explicitly modeled. However, partitioning of variance according to trait, method, and random error components showed that informant reports often exhibited less than 50% variance attributable to the trait factor under investigation. Implications of the findings are discussed for those marketing studies which focus on organizations or organizational subunits as the unit of analysis.